The Relevance of Traditional Islamic Boarding School Education in the Modernization Era - Segaf Baharun (Adabuna)
Traditional Islamic boarding schools are still relevant to be maintained. In facing the global era which is accompanied by modernization in all areas of life, Islamic boarding schools must continue to strive to maintain their existence and adapt to the conditions that surround them without abandoning their Islamic boarding school characteristics. In this study the researchers used a descriptive qualitative approach. The theory of a descriptive qualitative approach is a research method in which the results of the research are in the form of descriptive data. The relevance of the education system at the Mambaul Hikam Blitar Islamic Boarding School in the Modernization Era is shown by the existence of the latest programs by incorporating the state curriculum and opening public schools, the traditional learning system (halaqah) that applies to traditional Islamic boarding schools are provided in a balance with a modern learning system. Included in the curriculum, pesantren no longer only provide Islamic religious studies, but also modern general sciences which are accommodated from the government's curriculum.